The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3389/fendo.2019.00440
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Thyroid Dysfunction in Patients With Type 2 Diabetes Mellitus

Abstract: Background: Thyroid dysfunction has been widely reported among persons with diabetes (DM) in other parts of the World. In Nigeria, few studies have been reported. This study focused on risk factors for thyroid dysfunction in type 2 diabetes mellitus (T2DM) patients and will therefore add to the Nigerian literature, more so, as it is the first in South-East Nigeria. Objective: To determine the risk factors of thyroid dysfunction in patients with Type 2 DM. Methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
33
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 49 publications
7
33
2
Order By: Relevance
“…Subclinical hypothyroidism or hypothyroidism was reported to be the most common form of TD in several studies [6][7][8][9]. In this study, a relatively high prevalence of TD was found, among which low T3 syndrome constituted the majority.…”
Section: Discussionsupporting
confidence: 50%
“…Subclinical hypothyroidism or hypothyroidism was reported to be the most common form of TD in several studies [6][7][8][9]. In this study, a relatively high prevalence of TD was found, among which low T3 syndrome constituted the majority.…”
Section: Discussionsupporting
confidence: 50%
“…Subclinical hypothyroidism or hypothyroidism was reported to be the most common form of thyroid dysfunction in several studies [6][7][8][9]. In this study, a relatively high prevalence of thyroid dysfunction was found, among which low T3 syndrome constituted the majority.…”
Section: Discussionsupporting
confidence: 48%
“…[13] patient with type II diabetes problem are also at a risk of thyroid dysfunction. [14,15] although the risk is not as great as that for a Type I diabetic. [11] This is due to Type I diabetes being an autoimmune disease.…”
Section: Introductionmentioning
confidence: 97%
“…Different blood groups associated with DM and Thyroid disorderTypes of thyroid disorder accompanies with Diabetes Mellitus are illustrated infigure 6, which showed that hypothyroidism were more common in patients with DM by about 56% against 44% of hyperthyroidism. This case could be explained by the overproduction of thyroid hormones induced by the metabolism of sugar in human body [15]. types of thyroid disorders in DM patients…”
mentioning
confidence: 99%